PERAN EXTERNAL ASSURANCE DALAM MEMPERKUAT PENGARUH PENGUNGKAPAN ENVIRONMENTAL, SOCIAL, AND GOVERNANCE (ESG) TERHADAP COST OF DEBT (Studi Kasus pada Perusahaan Nonfinansial yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2022) - Tujori S, Abas; Ratmono, Dwi (Diponegoro Journal of Accounting, 2024)
The research activities carried out aim to investigate the influence of external assurance in influencing the relationship between environmental, social, and governance (ESG) disclosure and the cost of debt of companies in Indonesia in 2020-2022. This research use ESG disclosure which is measured using the content analysis method as an independent variable, cost of debt as a dependent variable, and external assurance as moderating variable.This research uses a population, namely non-finansial companies listed on the Indonesia Stock Exchange in 2020-2022. Using purposive sampling, the total research sample used after elimination was 253 data observation. The analytical method used in this research is multiple linear regression analysis using the E-views 12 application to carry out classical assumption tests and hypothesis tests.Based on this research, ESG disclosure by companies in Indonesia is still in medium category, where companies disclose more information on the governance dimension than on the environmental and social dimensions. This indicates that there is large room for companies in Indonesia to improve their ESG disclosure. The findings in this research show that ESG disclosure has a significant negative effect on the cost of debt. However, the moderating variable is still unable to significantly strengthen the negative influence of ESG disclosure on the cost of debt companies in Indonesia recorded on the IDX in 2020-2022.